2010
DOI: 10.1017/s1368980010002685
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and their associations with health behaviours in Korea

Abstract: Objective: Dietary habits, including dietary patterns, have been associated with the risk of chronic diseases, including cancer. The objective of the present study was to evaluate Korean dietary patterns as assessed by using an FFQ and associations of dietary patterns with lifestyle risk factors. Design: Dietary patterns were analysed by factor analysis using a sixteen-group FFQ. The associations between dietary patterns and lifestyle risk factors were investigated by logistic regression analysis. Setting: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…Therefore, this finding confirmed the conclusion that smoking is associated with less healthy dietary behavior regardless of culture, ethnicity or region. Korean male smokers have similar tendencies to results from preceding studies to follow a 'Sugar & fat' pattern and drink strong alcohol more, but eat less fruit and dairy products (10, 20). In contrast to Western studies, however, our study differs in the consumption of seaweed, starches, and meat.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Therefore, this finding confirmed the conclusion that smoking is associated with less healthy dietary behavior regardless of culture, ethnicity or region. Korean male smokers have similar tendencies to results from preceding studies to follow a 'Sugar & fat' pattern and drink strong alcohol more, but eat less fruit and dairy products (10, 20). In contrast to Western studies, however, our study differs in the consumption of seaweed, starches, and meat.…”
Section: Discussionsupporting
confidence: 69%
“…Also, Korean male smokers consumed less calcium but more coffee and alcohol, which is obviously detrimental to their bone health (9). There is even a theory suggesting that caffeinated or alcoholic beverages may enhance the taste of smoking (10). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering of life-style habits with different diet patterns has been reported previously, showing that a healthy diet leads to healthy behaviours and vice versa ( 13 , 38 ) . In the present study, we found a lower proportion of the population in both the fruit and vegetable and seafood and yogurt patterns who smoked.…”
Section: Discussionsupporting
confidence: 61%
“…Concerning the criteria used to group the foods obtained from collecting food intake data (step before the input of data in the multivariate techniques), 22% (n = 42) used preexisting groups from the FFQ, 14% (n = 26) adopted as a criterion the nutritional composition, 26% (n = 46) did not present any information about the used criteria, and remaining 38% (n = 75) reported: official agencies/dietary 164,172,187,191,193,198,203,204) 168,170,[174][175][176]178,179,183,184,[186][187][188][190][191][192][193]198,199,204,205) On the basis of the names of the foods 25 (42) 14 (24) 143,144,148,156,160,162,163,169,171,172,181,182,185,192,194) PCA: principal component analysis; FA: factor analysis; RRR: reduced regression rank; CVD: cardiovascular diseases; FFQ: Food Frequency Questionnaire; 24HR: 24-hour dietary recall. *Combination of two or more criteria within the same characteristic.…”
Section: Resultsmentioning
confidence: 99%